Pulmonary hypertension associated with busulfan. (1st September 2021) - Hagenburg, Jean; Savale, Laurent; Lechartier, Benoit; Ghigna, Maria‐Rosa; Chaumais, Marie‐Camille; Jaïs, Xavier; Sitbon, Olivier; Humbert, Marc; Montani, David
Abstract : Busulfan is widely used to treat malignant diseases, particularly for therapeutic intensification prior to an autologous stem cell graft. Numerous side effects consecutive to busulfan are described, but few descriptions of pulmonary hypertension exist, while bronchiolitis obliterans remains a rare complication. We report the clinical observations of four patients from the French Pulmonary Hypertension Registry who experienced subacute pulmonary hypertension after receiving busulfan as preparation regimen before an autologous stem cell graft for malignancies (Hodgkin's disease, Ewing's sarcoma and primary large B cell lymphoma of the brain). Patients experienced severe pulmonary arterial hypertension 2 to 4.5 months after busulfan administration. Pulmonary hypertension improved after treatment with approved drugs for pulmonary arterial hypertension and/or corticosteroids. During the follow‐up period, two patients developed chronic respiratory insufficiency due to interstitial lung disease, leading to double lung transplantation. The pathological assessment of explanted lungs revealed interstitial lung fibrosis with advanced bronchiolar lesions and severe pulmonary vascular damage. Three of the four patients were still alive after 36 to 80 months and the fourth died unexpectedly and suddenly after 5 months. In conclusion, PAH is a rare but severe complication associated with busulfan chemotherapy in adults. Histological examinations provide evidence for diffuse pulmonary vascular damage combined with interstitial lung injury in most cases.